Arietta Jarosława Iwaszkiewicza - Wiśniewski, Jerzy (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
Arietta, written in the final months of Iwaszkiewicz’s life (1894–1980), is one of a cycle of poems Music for a String Quartet from his posthumously published volume of poetry Music in the Evening (1980). Like all the poems from this cycle, it is a short poetic “narration” the central them of which is an image of an old man waiting for death. However, the structure of Arietta distinguishes the poem from other works. Unlike other poems consisting mostly of two four-line rhymed stanzas, Arietta is the only free verse, which is decidedly different from the metrical scheme used by Iwaszkiewicz in this part of the volume. In order to express one of the most crucial experiences in life, the poet crosses the borders of the formerly used model of communication (a poem-song), creating a new unique form of a poem-arietta and imitating the basic structural pattern of a musical arietta — a cavatina. An excerpt from Goethe’s Wanderers Nachtlied, slighly changed when quoted at the end of Arietta (“Warte nun balde / Ruhest du auch”), can be read as an encouragement to experience patient, fear-free waiting for the end of life, but it can also be understood as a kind of “singing” which gives you courage to face death. This final “arioso” in Iwaszkiewicz’s poem is not only a pacifying lullaby but also an expression of heroic waiting for irrevocable death.